Amphiphilic drug slow release microspheres fabricated using polyvinyl alcohol, 10‐Undecen‐1‐ol, and multi‐walled carbon nanotubes. Issue 7 (7th December 2022) - Tian, Pan; Liu, Wanjing; Yang, Shengdu; Zhang, Junhua
Abstract: In this paper, novel embolic microspheres with efficient drug delivery and slow drug release properties were developed, which have potential applications in transarterial chemoembolization (TACE). The microspheres were prepared by suspension polymerization using vinyl acetate, 10‐Undecen‐1‐ol (UO), multi‐walled carbon nanotubes, and crosslinking agent (1, 4‐butanediol divinyl ether). In the process, porous titanium tubes are used to control the particle size of the microspheres. In addition, the introduction of long‐chain (UO) makes the microsphere good swelling property in acetone. Multi‐walled carbon nanotubes modified by hexadecyltrimethoxysilane (HDTMS) are helpful for increasing both spherical morphology stabilization and swelling properties in acetone as well (C‐PVA‐2UO/CNT). Target drug was dissolved in acetone and the mcirospheres were dispersed in acetone to realize drug load. In vitro biocompatibility analysis showed that C‐PVA‐2UO/CNT is non‐cytotoxic and hemocompatible. The sustained drug release properties of C‐PVA‐2UO/CNT were confirmed by drug indomethacin (IMC) loading and release experiments. These findings suggest that the newly developed C‐PVA‐2UO/CNT has great potential to be used as a drug‐loaded embolization agent. Abstract : Amphiphilic drug slow release microspheres fabricated using polyvinyl alcohol, 10‐Undecen‐1‐ol, and multi‐walled carbon nanotubes.